2019
DOI: 10.1126/science.aau9072
|View full text |Cite
|
Sign up to set email alerts
|

Choline acetyltransferase–expressing T cells are required to control chronic viral infection

Abstract: Although widely studied as a neurotransmitter, T cell–derived acetylcholine (ACh) has recently been reported to play an important role in regulating immunity. However, the role of lymphocyte-derived ACh in viral infection is unknown. Here, we show that the enzyme choline acetyltransferase (ChAT), which catalyzes the rate-limiting step of ACh production, is robustly induced in both CD4+ and CD8+ T cells during lymphocytic choriomeningitis virus (LCMV) infection in an IL-21–dependent manner. Deletion of Chat wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 24 publications
6
95
0
1
Order By: Relevance
“…1) 38 . Another possible source of ACh are subpopulations of T cells that have been shown to code for ChAT 58 . ACh released from tuft cells, alone or together with ACh from local nerve endings and local T cells, can be expected to influence in a paracrine manner diverse epithelial cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1) 38 . Another possible source of ACh are subpopulations of T cells that have been shown to code for ChAT 58 . ACh released from tuft cells, alone or together with ACh from local nerve endings and local T cells, can be expected to influence in a paracrine manner diverse epithelial cells, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with selective Chat deficiency within the T cell compartment have impaired vasodilation in response to infection, decreased migration of antiviral T cells into infected tissues, and substantially compromised control of chronic LCMV clone 13 infection. These findings represent a genetic proof of function for ChAT in T cells during viral infection and implicate ChAT-expressing T cells in antiviral immunity (Cox et al, 2019).…”
Section: The Collateral Scientific and Therapeutic Benefitmentioning
confidence: 63%
“…Another very recent study revealed the important role of lymphocyte-released acetylcholine in the regulation of chronic viral infections. Lymphocytic choriomeningitis virus (LCMV) infection is associated with significantly increased ChAT levels in both CD4 + and CD8 + T cells in an IL-21-dependent manner (Cox et al, 2019). Mice with selective Chat deficiency within the T cell compartment have impaired vasodilation in response to infection, decreased migration of antiviral T cells into infected tissues, and substantially compromised control of chronic LCMV clone 13 infection.…”
Section: The Collateral Scientific and Therapeutic Benefitmentioning
confidence: 99%
“…In the BALT and peri-bronchial lung regions, multiple sources of ACh may contribute to cholinergic signaling whereas the alveolar space is relatively inaccessible to ACh secreted by bronchial epithelium or the vagal nerve. In addition, although our studies did not determine the primary inducers of ACh secretion by the cholinergic lymphocytes, previous studies have shown that cholinergic lymphocytes produce ACh in response to specific antigen, TLR agonists, neurotransmitters, and cytokines (11)(12)(13)47). As yet we do not know if local neurotransmitter secretion plays any role in lymphocyte ACh production The importance of ACh in recovery was indicated by the increased inflammation and aberrant tissue repair noted when Ach synthesis was inhibited.…”
Section: Discussionmentioning
confidence: 77%
“…Vagal nerve derived norepinephrine (NE) induces ACh release from cholinergic CD4 + T cells in the spleen, whereas cholinergic B-1 cells in the peritoneal cavity release ACh in response to TLR agonists, surface Ig ligation, and cholecystokinin (CCK) (11,12). During chronic hepatitis, both CD4 and CD8 cells secrete ACh in response to IL-21 (13).…”
Section: Introductionmentioning
confidence: 99%